A Viral Study On Conjunctivitis, Its Causes, Symptoms And Treatment Methods - Shwalla, Ahmed Jassim (Medical Science Journal for Advance Research, 2023)
Background: The virus has a very small body made of protein and nucleic acid, which is what gives it its size. It can pass through filters known as filterable filters because they stop the passage of microorganisms like bacteria. The ability to bypass filters, which is specific to viruses, is the only feature to which the name alludes. Adenoviruses and viruses in general are responsible approximately 80% of cases of acute conjunctivitis overall. Herpes and enterovirus are frequent causes of disease. In general, viral conjunctivitis spreads very easily and is widespread. And to control the spread of the disease and this type of virus, it is very necessary to diagnose diseases very quickly, strictly and strictly implement the laws of hand washing, and sterilize surfaces with sterilizers and alcohol. Swelling of the lymph node in front of the ear can sometimes occur when infected with the aforementioned virus.